TELAAH FILOSOFIS DAN LEGALISTIK DALAM PROSES LEGISLASI HUKUM ISLAM - Lutpillah; Muhammad Hamim; Muhammad Rasyid; Siti Fatimah (Institut Agama Islam Darul Ulum Kandangan, 2025)
This article critically examines the philosophical and legalistic dimensions in the legislative process of Islamic law within a modern nation state framework. The study is motivated by the growing tension between the ethical-substantive values of Islamic jurisprudence and the formal technical requirements of statutory law. Using a normative juridical approach combined with philosophical hermeneutics, the research analyzes how maqaṣid al-shari’ah informs legislative intent while conforming to constitutional and procedural legality. The findings reveal that successful Islamic legislation requires a dialectical synthesis: philosophical grounding ensures normative legitimacy and justice, while legalistic precision guarantees enforceability and systemic coherence. The study concludes that neglecting either dimension risks producing laws that are either ethically hollow or practically unenforceable. Keywords: constitutional legality, Islamic legislation, legal formalism, legal philosophy, maqaṣid alshari’ah